HOMOCYSTEINE AS A PREDICTOR OF CLINICAL OUTCOMES IN PATIENTS HOSPITALIZED FOR COVID-19 - Aleksic, Sanja; Ratinac, Milos (Srpski medicinski časopis Lekarske komore, 2022)
Introduction: COVID-19 is still a global health, social and economic problem. Treating this systemic infection remains a challenge. Numerous biomarkers have been studied so far as potential prognostic parameters, hematological and inflammation parameters most of all.Aim: Our main goal is to examine the association of homocysteine values with the outcome of the disease, as well as whether its value changes through the course of the disease.Methods: In our research, blood samples were collected from 131 patients who were SARS-CoV-2 positive and were treated at the University Clinical Center of Kragujevac. Inclusion criteria were as follows: men and women above 18 years of age, a signed informed consent for participation in the study, patients who were SARS-CoV-2 positive for the first time (which was confirmed by rapid Ag test or PCR test), who were treated in hospital and had any of the three forms of the disease. Blood samples were taken on the first, fifth and tenth day of the hospitalization period and the course of the disease was monitored. Statistical data processing was done using the IBM SPSS Statistics v.21 program.Results: In our research, we concluded that the value of homocysteine changed during the hospitalization period and that it had a growing trend. There was a statistical significance between the values measured on the first, fifth and tenth day. We showed that the patients suffering from hypertension (HTA) had higher values of the examined parameter compared to the patients who were not hypertensive. It was also observed that homocysteine value increased with age. There was a statistical significance between homocysteine values and the outcome of the disease.Conclusion: Based on our study, we can say that patients with high homocysteine levels (on the fifth day of the hospitalization period) have a worse outcome than patients with lower homocysteine levels. Patients with lower homocysteine levels have a better chance of recovery.
Keywords: homocysteine; COVID-19; disease outcome